Cutting edges : contemporary collage - Klanten, Robert; Hellige, Hendrik; Gallagher, James (Berlin : Gestalten, 2011)
Showcases a collection of contemporary collage artwork from around the world, which combines traditional materials with computer technologies, and includes an essay about the art form's history.
Includes index.
boek